2016
DOI: 10.1007/s11325-016-1340-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term CPAP treatment improves asthma control in patients with asthma and obstructive sleep apnoea

Abstract: Purpose Both asthma and obstructive sleep apnoea cause sleep disturbance, daytime sleepiness and diminished quality of life. Continuous positive airway pressure (CPAP) is efficient in reducing symptoms related to sleep apnoea. Here we report the impact of long-term use of CPAP on asthma symptoms. Methods A survey questionnaire was distributed to all of our obstructive sleep apnoea patients with CPAP therapy in 2013. We used the Finnish version of the Asthma Control Test™ (ACT) and a visual analogue scale (0 = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 34 publications
0
34
1
2
Order By: Relevance
“…Our findings are of clinical relevance because they underline that asthmatic patients are under‐referred for sleep studies, despite the existing evidence of a high prevalence of OSA in asthma (Kong et al., ) and the positive effects of OSA treatment on asthma control (Kauppi et al., ; Wang et al., ). The prevalence of physician‐diagnosed asthma in our cohort was of the same order of magnitude as the prevalence rate of asthma recently found in CPAP‐treated patients (Turino et al., ).…”
Section: Discussionmentioning
confidence: 66%
“…Our findings are of clinical relevance because they underline that asthmatic patients are under‐referred for sleep studies, despite the existing evidence of a high prevalence of OSA in asthma (Kong et al., ) and the positive effects of OSA treatment on asthma control (Kauppi et al., ; Wang et al., ). The prevalence of physician‐diagnosed asthma in our cohort was of the same order of magnitude as the prevalence rate of asthma recently found in CPAP‐treated patients (Turino et al., ).…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, although ACT is a simple tool in the busy clinic setting, further history taking by the physicians or use of more detailed questionnaires would be necessary to assess the patient's response to treatment. A previous study showed that long‐term CPAP treatment improved asthma control, with improvement of ACT from 15.4 to 19.8 but the reliability of the patients’ responses was questionable as patients needed to recall their CPAP usage from many years earlier. Nevertheless, the current RCT has shown that CPAP treatment for 3 months improved daytime sleepiness, quality of life and the domains of vitality in the SF‐36 questionnaires, as also shown by a previous prospective observational study …”
Section: Discussionmentioning
confidence: 99%
“…The AHI is significantly associated with the occurrence of severe asthma exacerbations (4). Researchers have found that long-term treatment of CPAP in patients with both asthma and obstructive sleep apnoea can decrease the asthma symptoms and improve asthma control and quality of life (9,10). Since evaluating OSA in patients with asthma has been included in the Guidelines for the Diagnosis and Management of Asthma (21), there is a need for clinical investigations of early and periodic detection of OSA among asthma populations.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic data showed that the prevalence of OSA among asthmatic populations ranges from 38% up to as high as 70% (7). There is growing evidence that continuous positive airway pressure (CPAP) in adults and adenotonsillectomy in children which are recommended as first line treatment of OSA can improve their asthma symptoms (8)(9)(10). Mild OSA in severe asthma patients is associated with increased proportion of neutrophils in sputum and changes in airway remodeling (11,12).…”
Section: Introductionmentioning
confidence: 99%